2013
DOI: 10.1007/s00426-013-0530-8
|View full text |Cite
|
Sign up to set email alerts
|

Tracking the attentional blink profile: a cross-sectional study from childhood to adolescence

Abstract: This cross-sectional study is the first to examine the developmental trajectory of temporal attention control from childhood to adolescence. We used a rapid serial visual presentation paradigm, calling for the identification of two targets (T1 and T2) embedded in a distractor stream. In adults, manipulating the lag time within the target doublet typically leads to pronounced impairment in report for T2, when it follows T1 after approximately 200 ms, with one intervening distractor (lag 2); this is referred to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
0
7
1
Order By: Relevance
“…In contrast to other developmental work, which has shown both increases (Dye & Bavelier, 2010; Garrad-Cole et al, 2011; Heim et al, 2015) and decreases (Russo, 2016) in the depth of the AB as a function of age until around age 15, the decrease in accuracy in the time frame of the AB in the present study was approximately 13%, and this was the case for all three age groups. These findings suggest that on a feature binding task, the AB is mature by the age of approximately 10 years, despite a systematic increase in overall target accuracy with age.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to other developmental work, which has shown both increases (Dye & Bavelier, 2010; Garrad-Cole et al, 2011; Heim et al, 2015) and decreases (Russo, 2016) in the depth of the AB as a function of age until around age 15, the decrease in accuracy in the time frame of the AB in the present study was approximately 13%, and this was the case for all three age groups. These findings suggest that on a feature binding task, the AB is mature by the age of approximately 10 years, despite a systematic increase in overall target accuracy with age.…”
Section: Discussioncontrasting
confidence: 99%
“…Modelling these data using the Episodic Simultaneous Type, Serial Token model (eSTST;(Wyble, Bowman, & Nieuwenstein, 2009), suggested that the development of inhibitory control mechanisms could account for both the findings of an increasing AB depth with age, and of a concomitant decrease in the number of swaps, a type of error where participants report both targets, but do so in the wrong order. These modelling findings suggest that inhibition plays a key role in the development of temporal visual attention, with an important transition occurring around age 10 (Garrad-Cole, Shapiro, & Thierry, 2011; Heim, Benasich, Wirth, & Keil, 2015; Russo et al, 2016). This task related distinction is particularly important as Dale, Dux, & Arnell, (2013) suggest that although different types of tasks that measure the AB seem to share common variance, tasks that include a set-shifting component also have unshared variance that cannot be attributed to the AB among adults.…”
Section: Developmental Studies Of the Abmentioning
confidence: 78%
See 1 more Smart Citation
“…First, our findings that the AB duration is relatively preserved in children when using a simple task differs from the findings of previous explorations of the AB in children, which found a protracted duration of the AB, and presumably results from the difference in the tasks used to elicit the AB. All of the AB tasks reported in the literature (Dye & Bavelier, 2011; Garrad‐Cole et al., ; Heim et al., ; Heim et al., , Experiment 1), with the exception of one, used complex tasks that either required participants to shift their attentional set, or had complex stimuli in which targets and distractors shared multiple features. For example, in the two studies by Heim et al, participants had to detect a first target, which consisted of a drawing of a mode of transportation (e.g., a boat, a car, or a bicycle), and a second target that was a shape (e.g., a circle, triangle, or square), among distractors that consisted of symbols.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is important to note that differences between task requirements affect the characteristics of the AB and presumably the appearance of its developmental course. Most developmental studies of the AB use a task in which the two targets, T1 and T2 are defined by different criteria (e.g., Heim, Wirth, & Keil, , Experiment 1; Heim et al., ) or tasks that are complicated by the conjunction of targets and distractors (Dye & Bavelier, ; Garrad‐Cole et al., ). For example, Heim, Wirth, and Keil () asked participants to first detect a green mode of transportation (e.g., an airplane) and then a green shape (e.g., a circle) among other shape distractors (and recall the identity of both targets at the end of the stream).…”
Section: Introductionmentioning
confidence: 99%